2016
DOI: 10.1038/srep28614
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of DNA Polymerase β R137Q Results in Retarded Embryo Development Due to Impaired DNA Base Excision Repair in Mice

Abstract: DNA polymerase β (Pol β), a key enzyme in the DNA base excision repair (BER) pathway, is pivotal in maintaining the integrity and stability of genomes. One Pol β mutation that has been identified in tumors, R137Q (arginine to glutamine substitution), has been shown to lower polymerase activity, and impair its DNA repair capacity. However, the exact functional deficiency associated with this polymorphism in living organisms is still unknown. Here, we constructed Pol β R137Q knock-in mice, and found that homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…We find increased number of colocalized γH2AX and p53BP1foci in senescing cells, which is amplified by loss of Polβ . We should note that DSB have been shown to accumulate in a knock‐in mouse model of PolB variant R137Q [Pan et al, ], Polβ ‐/‐ cells exposed to MMS [Pascucci et al, ], and an Alzheimer's/Polβ +/ ‐ mouse (3xTgAD/ Polβ ) [Sykora et al, ]. But this is the first report that loss of Polβ alone results in a significant accumulation of colocalized γH2AX and p53BP1, presumed to be DSB.…”
Section: Discussionmentioning
confidence: 98%
“…We find increased number of colocalized γH2AX and p53BP1foci in senescing cells, which is amplified by loss of Polβ . We should note that DSB have been shown to accumulate in a knock‐in mouse model of PolB variant R137Q [Pan et al, ], Polβ ‐/‐ cells exposed to MMS [Pascucci et al, ], and an Alzheimer's/Polβ +/ ‐ mouse (3xTgAD/ Polβ ) [Sykora et al, ]. But this is the first report that loss of Polβ alone results in a significant accumulation of colocalized γH2AX and p53BP1, presumed to be DSB.…”
Section: Discussionmentioning
confidence: 98%
“…This effect has been further confirmed in a pol βR137Q transgenic mouse model in vivo in a recent study [79]. The results of the studies suggest that the pol β polymorphic variant exhibits significantly reduced DNA synthesis activity in random DNA sequence compared with wild-type pol β, and this may result in genome instability.…”
Section: Discussionmentioning
confidence: 66%
“…We demonstrated that this was because the polymorphic variant exhibited similar capability to that of wild-type pol β of skipping over a small template loop structure during BER ( A previous study has shown that pol βR137Q exhibits 30% of wild-type enzymatic activity in the context of random sequence, which in turn reduces BER capacity and increases cellular sensitivity to alkylating DNA damaging agents as well as promotes apoptosis [61]. This effect has been further confirmed in a pol βR137Q transgenic mouse model in vivo in a recent study [62]. The results of the studies suggest that the pol β polymorphic variant exhibits significantly reduced DNA synthesis activity in random DNA sequence compared with wild-type pol β, and this may result in genome instability.…”
Section: Pol βR137q Variant Skips Over a Small Loop On The Template Smentioning
confidence: 76%
“…In addition, the heterozygous pol β variant with deletion of exon 4-6 and 11-13 is associated with an increased risk of ovarian carcinoma [60]. In addition, some functional studies of polymorphic variants of BER enzymes also revealed a linkage between variants of BER enzymes and cancers [61,62].…”
Section: Figure I4 Base Excision Repair Pathway [8]mentioning
confidence: 99%
See 1 more Smart Citation